2021
DOI: 10.3390/polym13152469
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Polyurethane Foams Modified with a Mixture of Bio-Polyols of Different Chemical Structures

Abstract: We report on rigid polyurethane (PUR) foams prepared using different contents of a mixture of two bio-polyols (20–40 php). The bio-polyols were obtained through epoxidation and a ring opening reaction. Different chemical structures of the bio-polyols resulted from the use of 1-hexanol and 1,6-hexanediol as opening agents. The bio-polyols were characterized by hydroxyl values of 104 and 250 mgKOH/g and viscosities of 643 and 5128 mPa·s, respectively. Next, the influence of the bio-polyols on the foaming process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…This is because the epoxide ring is more likely to decompose at higher temperatures, which can lead to the formation of smaller molecules such as aldehydes and ketones. 20 Mungroo et al (2008) also found that the optimised temperature in their study was 65°C. This is because the formation of unwanted by-products also increases at higher temperatures.…”
Section: Effect Of Temperature On the Rate Of Reactionmentioning
confidence: 76%
“…This is because the epoxide ring is more likely to decompose at higher temperatures, which can lead to the formation of smaller molecules such as aldehydes and ketones. 20 Mungroo et al (2008) also found that the optimised temperature in their study was 65°C. This is because the formation of unwanted by-products also increases at higher temperatures.…”
Section: Effect Of Temperature On the Rate Of Reactionmentioning
confidence: 76%
“…Fourier Transform Infrared (FTIR) spectroscopy was used to investigate the chemical characteristics of WCO and EWCO. The approach can be used to determine the presence of an oxirane ring in its epoxidized state and the C=C double bonds in crude oleic acid [22] . The existence of an oxirane ring may usually be recognised at wavenumbers ranging from 1100 to 1300 cm −1 and the double bond of C=C was disappeared after the reaction at 2900 cm −1 as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Rigid PUR foams were obtained using bio-polyols and petrochemical components. Two types of bio-polyols (HF polyol and LF polyol) were prepared at Cracow University of Technology, as described in previous works [23,24]. Bio-polyols were synthesised in a two-step process using rapeseed oil as the raw material.…”
Section: Methodsmentioning
confidence: 99%